ANALISIS PEMBENTUKAN JUDGEMENT AUDITOR PADA PENILAIAN RISIKO FRAUD: PERSPEKTIF BOUNDED RATIONALITY THEORY - Karolina Dyahayu Chandrasari; Eko Suwardi (Behavioral Accounting Journal, 2021)
External audit provides public confidence in the financial statements. However, the profession is very vulnerable to cases of fraud. So that the public's trust in the quality of the external auditors' judgement decreases. There have been many studies that discuss the factors that cause audit failure and audit quality. However, surprisingly little is known about the fundamental question: how does the rationality of individual auditors affect audit judgements? This study aims to describe the formation of auditor's judgement on fraud risk assessment using the bounded rationality model concepts. The author uses case study research with a qualitative approach. It involves a single unit of analysis in the form of an individual auditor, and discussion is carried out around the scope of the auditor's behavior by interview method. To describe the auditor's judgements, the bounded rationality model (Sharda et al., 2014) is used in the form of a combination of problem-solving concepts (Kaufman, 1992) and decision making (Simon, 1977) with a discussion associated with a socio-behavioral perspective (Gibbins, 1984). We found that the auditors adhered firmly to the template built from understanding the audit environment and systematically and sequentially described the three main processes of judgement formation in the form of simplification, validation, and rationalization. The model can also point out that not only is the satisficing concept involved, but the stopping rule concept also influences the formation of auditor judgement.